Explaining of the roll of the guiding principles in design problem understanding by vernacular architecture (Case study: Seraj-Mahaleh village) - Maryam Nouri; Shadi Azizi; Mohammad Reza Nasir Salami (مسکن و محیط روستا)
In the field of architecture, one of the branches of knowledge is design studies that studies on the design process. Researchers in this field have used various concepts to explain the designer's mental processes, one of them is the guiding principles. The guiding principles refer to the principles that the designer believes in and uses them to framerate and understand the priorities of the design problem. These principles, which rely on the design worldview, create a kind of unified approach fordealing with various design issues. Much of the research done in the design process and the role of the guiding principles in it has focused on architects and students who have been trained in urban environments and have faced design problems in the city. However, vernacular architecture in rural environments has very different coordinates and architectural production methods have valuable themes that can be extracted and studied. Vernacular architecture is an architectural style that is designed based on local needs, availability of construction materials and reflecting local traditions. At least originally, vernacular architecture did not use formally-schooled architects, but relied on the design skills and tradition of local builders. Therefore, the main question of this research is that what are the guiding principles in the design process of a vernacular architect and what are their content? To answer this question, Seraj- Mahaleh village was selected as an example alongside the body tissue and native social tissue. Sarej-Mahaleh village located in Kolbad district of Golgah city, 5 km from the city and 20 km from Behshahr city. Then five of the native architects of the region were identified. In the following, the architects presented three design issues with the theme "House" and they were asked to talk about their design. These words were recorded in semi-structured interviews and then analyzed by qualitative content. The overall structure of this research is based on a qualitative method. Qualitative research methodology is generally referred to as research, whose findings are not obtained through statistical processes and quantifiable purposes. Qualitative research is a broad methodological approach that encompasses many research methods. The aim of qualitative research may vary with the disciplinary background, such as a psychologist seeking to gather an in-depth understanding of human behavior and the reasons that govern such behavior. Qualitative methods examine the why and how of decision making, not just what, where, when, or "who", and have a strong basis in the field of sociology to understand government and social programs. In order to clarify the subject and gain better result, studies and backgrounds of this research, the sources and research backgrounds have been divided into two areas of study design, and rural house. Concepts extracted from these interviews show that being in harmony with nature, avoiding longevity, long-term customer and user satisfaction, as well as respecting neighborliness, is one of the most important principles that always comes into the face of the design problem of native architects. The guiding principles have a strong limiting role in the design process of vernacular architects. Every design issue does not start with a white tablet or null mind. Each designer has a specific worldview and carries a set of beliefs, values, and attitudes that we call "guiding principles." The relation between this approach to guiding principles versus non- vernacular architects is a topic can be considered in future research and it provides more complete understanding of design in the native environment.